Yield of TB screening in prisons in Tajikistan - S. Moe; M. Asozoda; A. Aung; Z. Dusmatova; F. Akintore; E. Nshimiyimana; A. Zavqibekov; N. Sitali; W.K. Mulanda; T. Cullip; A. Sinha (IJTLD Open)
BACKGROUND: The rate of TB in prison institutions is estimated to be 23 times higher than in the general population. Limited documentation exists regarding TB screening in Tajikistan's prisons. This study aims to report findings from a TB screening conducted in prison facilities in Tajikistan. METHODS: A systematic TB screening was conducted between July 2022 and September 2023, following a locally adapted algorithm based on WHO recommendations. The screening yield was calculated as the proportion of confirmed TB cases, with categorical variables compared using a χ 2 test. RESULTS: A total of 7,223 screenings were conducted, identifying 31 TB cases, including 17 drug-susceptible TB cases, eight drug-resistant TB cases, and six clinically diagnosed cases. The overall screening yield was 0.43%. Notably, the screening yield was 3.4% among individuals with at least one TB symptom and 0.03% among those without TB symptoms (P < 0.001). CONCLUSION: The identified rate of TB in these prisons is five times higher than in the general population. Symptomatic individuals had a higher likelihood of TB diagnosis, and using chest X-rays significantly improved screening yield. We recommend increasing the capacity for chest X-ray testing to enhance TB prevention and control within prison settings.